Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1589/jpts.25.1595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 Weeks of Accelerated Rehabilitation Exercise on Muscle Function of Patients with ACL Reconstruction of the Knee Joint

Abstract: [Purpose] To examine changes in the knee joint’s isokinetic muscle functions following systematic and gradual rehabilitation exercises lasting for 12 weeks for male and female patients who underwent anterior cruciate ligament (ACL) reconstruction. Differences in muscle functions between the uninvolved side (US) and the involved side (IS) before surgery, differences in muscle functions between US and IS after rehabilitation exercises lasting for 12 weeks, and changes in muscle functions on US and IS between bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…with our initial measurements. (Lee, Kim, Park, 2013). Researchers from Poland also demonstrated a positive effect of isokinetic exercises performed as part of a rehabilitation program in the period of 16-24 postoperative weeks, which was reflected in a statistically significant improvement in quadriceps torque at an angular velocity of 60 °/s.…”
Section: Discussionmentioning
confidence: 97%
“…with our initial measurements. (Lee, Kim, Park, 2013). Researchers from Poland also demonstrated a positive effect of isokinetic exercises performed as part of a rehabilitation program in the period of 16-24 postoperative weeks, which was reflected in a statistically significant improvement in quadriceps torque at an angular velocity of 60 °/s.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Lee et al 11 ) reported that extension and flexion at 60°/s significantly improved after accelerated rehabilitation training for 12 weeks after anterior cruciate ligament reconstruction. Moreover, the changes in the dynamic balance function were evaluated after the application of a rehabilitation exercise program following anterior cruciate ligament reconstruction, but no significant improvement was observed over time and no interaction effects were noted according to the groups and measurement periods in the affected knee.…”
Section: Discussionmentioning
confidence: 99%
“…In a 4 year study on injuries among female college volleyball players 24 ) , Agel et al also reported lower extremity injury rates of 58.7% during the season and 55.9% during training 25 ) . Given that muscle performance in jumping significantly relies upon lower-extremity extension strength in the knee and then the ankle joint, identifying muscle performance abnormalities may be useful for determining the causes of imbalance-induced functional instability and creating corrective strategies 26 ) . In a study in soccer players, Choi et al reported significant differences between knee extensor and flexor isokinetic strength (247.9 ± 34.4 Nm vs. 165.1 ± 29.4 Nm) and ascribed higher flexor strength in high-performing players to the fact that knee flexors play an important role in enhancing sprinting speed and stability in the execution of various motions involving the knee joint 27 ) .…”
Section: Discussionmentioning
confidence: 99%